Nächstes Jahr in Jerusalem – oder auch nicht. Perspektiven auf Deutschland und Israel in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" und Mirna Funks "Winternähe" - Spener, Anna Maria (DINGS 2021. Beiträge zur Digitalen INternationalen Germanistischen Studierendentagung. Literatur des 20. und 21. Jahrhunderts)

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice—A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Feedback processing in cognitive and motor tasks: A meta‐analysis on the feedback‐related negativity - Faßbender, Laura; Krause, Daniel; Weigelt, Matthias (Psychophysiology)
Abstract For motor learning, the processing of behavioral outcomes is of high significance. The feedback‐related negativity (FRN) is an event‐related potential, which is often described as a correlate of the reward prediction error in reinforcement learning. The number of studies examining the FRN in motor tasks is increasing. This meta‐analysis summarizes the component in the motor domain and compares it to the cognitive domain. Therefore, a data set of a previous meta‐analysis in the cognitive domain that comprised 47 studies was reanalyzed and compared to additional 25 studies of the motor domain. Further, a moderator analysis for the studies in the motor domain was conducted. The FRN amplitude was higher in the motor domain than in the cognitive domain. This might be related to a higher task complexity and a higher feedback ambiguity of motor tasks. The FRN latency was shorter in the motor domain than in the cognitive domain. Given that sensory information can be used as an external feedback predictor prior to the presentation of the final feedback, reward processing in the motor domain may have been faster and reduced the FRN latency. The moderator variable analysis revealed that the feedback modality influenced the FRN latency, with shorter FRN latencies after bimodal than after visual feedback. Processing of outcome feedback seems to share basic principles in both domains; however, differences exist and should be considered in FRN studies. Future research is motivated to scrutinize the effects of bimodal feedback and other moderators within the motor domain.
Keywords: Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; Biological Psychiatry; Cognitive Neuroscience; Developmental Neuroscience; Endocrine and Autonomic Systems; Neurology; Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; General Neuroscience

Imagine to automatize: automatization of stimulus–response coupling after action imagery practice in implicit sequence learning - Dahm, Stephan F.; Hyna, Henri; Krause, Daniel (Psychological Research)
Abstract Action imagery practice (AIP) describes the repetitive imagination of an action to improve subsequent action execution. Because AIP and action execution practice (AEP) draw on partly similar motor mechanisms, it was assumed that AIP may lead to motor automatization, which is observable in a reduction of dual-task costs after AEP. To investigate automatization in AIP, we compared dual-task and single-task performance in practice and random sequences in pretests and posttests. All participants practiced serial reactions to visual stimuli in ten single-task practice sessions. An AIP group imagined the reactions. An AEP group and a control practice group executed the reactions. Practice followed a sequential sequence in AIP and AEP but was random in control practice. In dual-task test conditions, tones were counted that appeared in addition to the visual stimuli. RTs decreased from pretest to posttest in both practice and random sequences in all groups indicating general sequence-unspecific learning. Further, RTs decreased to a greater extent in the practice sequence than in the random sequence after AIP and AEP, indicating sequence-specific learning. Dual-task costs—the difference between RTs after tone and no tone events—were reduced independent from the performed sequence in all groups indicating sequence-unspecific automatization. It is concluded that the stimulus–response coupling can be automatized by both, AEP and AIP.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Aufschieben, weil man sich schlecht fühlt, oder sich schlecht fühlen, weil man aufschiebt? – Gruppenspezifische Unterschiede im Verhalten und Erleben von Prokrastination - Bobe, Julia; Klingsieck, Katrin B.

Prokrastination und das schlechte Gewissen - Gruppenunterschiede im Erleben und Auftreten von Prokrastination. - Bobe, Julia; Klingsieck, Katrin B.

Simulation of Infrared Welded Short Fiber Reinforced Thermoplastic Parts based on Mori-Tanaka Homogenization Method - Schöppner, Volker; Gevers, Karina; Hoenen, N.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Advanced Structured Materials)

Verbesserung der Betriebspunktauslegung durch Schneckensimulation - Schöppner, Volker; Austermeier, Laura; Trienens, Dorte (Wissenschaftlicher Arbeitskreis Kunststofftechnik)

The main factors influencing glass fiber shortening in the processing of bulk molding compounds (BMC) - Moritzer, Elmar; Scholle, Maximilian

Optimizing the Processing Performance of a Single Screw Extruder Using Live Simulations Based on Real Time Experimental Data - Köllermeier, Jonas; Schöppner, Volker

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

The Wave Must Be Right - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Plastic Insights)

Vorspannkraftrelaxation bei der Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Novel Straightening-Machine Design with Integrated Force Measurement for Straightening of High-Strength Flat Wire - Bathelt, Lukas; Scurk, Maximilian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Sensors)
In a punch-bending machine, wire products are manufactured for a wide range of industrial sectors, such as the electronics industry. The raw material for this process is flat wire made of high-strength steel. During the manufacturing process of the flat wire, residual stresses and plastic deformations are induced into the wire. These residual stresses and deformations fluctuate over the length of the semi-finished product and have a negative effect on the final product quality. Straightening machines are used to reduce this influence to a minimum. So far, the adjustment of a straightening machine has been performed manually, which is a lengthy and complex task even for an experienced worker. This inevitably leads to the use of inefficient straightening strategies and causes high rejection rates in the entire production process. Due to a lack of sensor information from the straightening operation, application of modern feedback control methods has not been practicable. This paper presents a novel design for a straightening machine with an integrated, precise straightening force measurement. By simultaneously monitoring the position of the straightening rollers, state variables of the straightening operation can be derived. Additionally, a tension control for feeding the flat wire is introduced. This is implemented to mitigate the disturbing effects caused by irregularities in the wire-feeding process. In the results of this article, the high precision of the developed force measurement design and its possible applications are shown.

Selbstverständlichkeit und Problematisierung. Husserls Programm der Phänomenologie - Philippi, Martina
Selbstverständlichkeiten in Verständlichkeiten überführen – dies ist das Credo der Phänomenologie Husserls. Ein zentrales Anliegen des phänomenologischen Programms ist es, die „vermeintlichen Selbstverständlichkeiten“ des Positivismus aufzudecken und zu klären; zugleich gibt Selbstverständlichkeit Anlass zu inhaltlichen Analysen, denn sie fungiert als Geltungsmodus des alltäglichen Lebensvollzugs, gespiegelt im Sinnbild von Boden und Horizont der Lebenswelt. Die Studie stellt Geltung, Einstellung und Perspektivwechsel als jene begrifflichen Werkzeuge heraus, mit denen Husserl dieses schwer greifbare Phänomen systematisch erschließt und methodisch wie inhaltlich in die Spannungsfelder von Theorie und Praxis, Doxa und Episteme, Lebenswelt und Wissenschaft einbettet. Darüber hinaus ergänzt sie mit dem psychopathologischen Ansatz Wolfgang Blankenburgs, was die Beschreibungsmacht der Phänomenologie an ihre Grenzen bringt: die Erfahrung der Selbstverständlichkeit im Lebensvollzug.
Keywords: Selbstverständlichkeit; Husserl; Phänomenologie

The Submission of Rebellious Cities in the Roman-German Empire - Kamp, Hermann (Peacemaking and the Restraint of Violence in High Medieval Europe)

LibriWASN: A Data Set for Meeting Separation, Diarization, and Recognition with Asynchronous Recording Devices - Schmalenstroeer, Joerg; Gburrek, Tobias; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)

Achim Duchow: Blindes Vertrauen / Werkverzeichnis 1971–1993
Das Werkverzeichnis des Düsseldorfer Malers, Fotografen und Objektkünstlers Achim Duchow (1948 – 1993) lädt ein zur Wiederentdeckung eines komplexen OEuvres. Im spielerischen Umgang mit Autorschaft, Subjektivität und Medien, dem unmittelbaren Zugriff auf alle ihn bewegenden Themen ist ein Werk entstanden, das auch heute noch seine Wirkung entfaltet. In chronologischer Folge, unterbrochen von einzelnen Essays verzeichnet die Publikation als eine über 400-seitige Liste alle Phasen des Werks: Duchows Zusammenarbeit mit Sigmar Polke in den 1970er Jahren, seinen zweieinhalbjährigen Aufenthalt in Japan, seine Rückkehr 1981 in eine Kunstszene, die sich rasant in Richtung Marktgängigkeit verändert hatte, seine Arbeit an einem neuen Selbstverständnis als Künstler und Kulturarbeiter, seine malerische Auseinandersetzung mit deutscher Geschichte und Politik, mit Kolonialismus und Wiedervereinigung, aber auch mit dem Informel und dem Konstruktivismus. Das Werkverzeichnis katalogisiert alle auffindbaren Arbeiten sowie Texte von Duchow selbst. Weggefährt·innen und Historiker·innen geben einen Einblick in den radikalen Kontext seines Lebens.
Keywords: Malerei; Medienkunst; Fotografie; Düsseldorf; Hamburg; Japan; Bad Painting; Popart; Montage

Al Vostro Servizio - Schulze, Max (Buch Handlung Welt Bücher)
Buch Handlung Welt – in drei Worten − wurde von der Künstlerin Hilka Nordhausen 1976 im Hamburger Karolinenviertel eröffnet. Ein Laden, der Unmengen an Drucken, Heften, Broschüren, Taschenbüchern, Publikationen aus dem Underground, aus Übersee, der Kunst und Esoterik, auch selbstverlegte Bücher, Kataloge und Zines versammelte, die in wirren Stapeln halbhohe Tische bedeckten. Zwischen den überquellenden Bücherregalen fanden Lesungen und Performances statt, Filme und alles mögliche andere wurden projiziert. Fast jeden Monat entstand ein neues Wandbild in den Räumen. Die Buch Handlung Welt war bis 1983 in Hamburg der Ort für selbstorganisiertes künstlerisches Handeln − ein Anschlag auf die Wirklichkeit. Ein Konvolut dieser Bücher und Zeitschriften befindet sich im Nachlass von Hilka Nordhausen. 40 Jahre später stellt sich die Frage: Was bleibt von den Büchern, welchen Zeitgeist transportieren sie? Welche haben auch heute noch Bedeutung? Dieses Buch versammelt eine Reihe von subjektiven und widersprüchlichen Einschätzungen zu diesen Titeln, von jungen und mittelalten Künstler*innen und Wissenschaftler*innen.
Keywords: Buch Handlung Welt; Hilka Nordhausen; Achim Duchow; Martin Kippnberger